Blood coagulation estimation using the method of laser-speckle correlation; Proceedings of SPIE; Vol. 11065 : Saratov Fall Meeting 2018: Optical and Nano-Technologies for Biology and Medicine - Li Lin; Lyushnevskaya (Sytnik) Yu. D. Yuliya Dmitrievna; Pekker Ja. S. Jakob Semenowitsch; Gubarev F. A. Fedor Aleksandrovich (2019, 2019)
Title screen